Exploring the Impact of the Pandemic on Reference and Research Services: A Literature Review. Issue 3 (3rd July 2021) - Osorio, Nestor L.; Droog, Alissa
Abstract: This literature review explores the impact of COVID-19 on reference and research services in academic libraries. The first half of the review identifies changes and initiatives during the previous ten years using meaningful examples of changes. Gathering information from listservs, conference schedules, trade publications, websites, and emerging research, the second half of this review revisits changes to reference and research services from Spring 2020-Summer 2021. The literature is extensive, for that reason, we have identified meaningful experiences that can be translated into the pre- and intra-pandemic service practices. The pandemic advanced many existing and emerging trends, allowed libraries to find innovative solutions to new problems, and paused other areas. While this literature review cannot predict the future, it will allow readers to reflect on real case experiences with the expectations that our work will enlighten others in creating or adapting services for a new generation of reference and research services.